2022
DOI: 10.3389/fphar.2022.1010483
|View full text |Cite
|
Sign up to set email alerts
|

Catalpol ameliorates CFA-induced inflammatory pain by targeting spinal cord and peripheral inflammation

Abstract: Chronic, inflammatory pain is an international health concern that severely diminishes individuals’ quality of life. Catalpol is an iridoid glycoside derived from the roots of Rehmannia glutinosa that possesses anti-inflammatory, antioxidant, and neuroprotective properties for the treating multiple kinds of disorders. Nevertheless, catalpol’s impacts on inflammatory pain and its potential methods of action are still unclear. The purpose of this investigation is to determine the mechanism of catalpol to reduce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…[21] The anti-inflammatory effect of rehmannia glutinosa is also particularly obvious, and its active ingredient catalpol can significantly decreased the expression of NF- κ B/NLRP3 inflammatory axis and inflammatory factors, inhibit tissue inflammation and relieve pain. [22] Meanwhile, its active ingredient aucubin also has anti-inflammatory and antioxidant pharmacological effects. [23] Pyrola extract inhibits phosphorylation of p38 MAPK and NF- κ B, inhibits the expression of inducible nitric oxide synthase inducible nitric oxide synthase, iNOS and exerts anti-inflammatory effects.…”
Section: Discussionmentioning
confidence: 99%
“…[21] The anti-inflammatory effect of rehmannia glutinosa is also particularly obvious, and its active ingredient catalpol can significantly decreased the expression of NF- κ B/NLRP3 inflammatory axis and inflammatory factors, inhibit tissue inflammation and relieve pain. [22] Meanwhile, its active ingredient aucubin also has anti-inflammatory and antioxidant pharmacological effects. [23] Pyrola extract inhibits phosphorylation of p38 MAPK and NF- κ B, inhibits the expression of inducible nitric oxide synthase inducible nitric oxide synthase, iNOS and exerts anti-inflammatory effects.…”
Section: Discussionmentioning
confidence: 99%
“…Catalpol can be effective for the relief of chronic inflammatory pain. Zhao et al found cytotoxicity at catalpol concentrations of 1000 μM, while subcutaneous administration of catalpol (2.5 and 10 mg/kg) reduced peripheral pain by inhibiting tissue inflammation in a dose-dependent manner (Zhao et al, 2022).…”
Section: Chronic Inflammatory Painmentioning
confidence: 99%
“…Catalpol is an iridoid glucoside extracted from the rhizome of rehmanniae , with molecular formula, C 15 H 22 O 10 (Figure 1) (Bhattamisra et al, 2020). Studies have shown that catalpol has various biological activities, such as anti‐inflammatory, antitumor, neuroprotective, and anti‐glycemic (Liu, Du, et al, 2022; Yap et al, 2020; Zhao et al, 2022). The anti‐inflammatory activity of catalpol has been widely studied.…”
Section: Introductionmentioning
confidence: 99%